2022
DOI: 10.21608/ejcm.2022.139768.1222
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Occupational Risk Factors of Low Back Pain among Health Care Workers in Operating Rooms at Mansoura University Main Hospital

Abstract: Background: Low back pain (LBP) is a public health concern worldwide and is a common cause of work-related disorder particularly in health-care workers (HCWs) including doctors, nurses and technicians. Objective: The objective of the current study is to estimate the prevalence, risk factors, and characteristics of LBP among HCWs in operation rooms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 24 publications
2
2
0
Order By: Relevance
“…The link between getting older and developing lower back pain is complicated and can be further complicated by several other factors. According to the findings of the study by Alemam (2022), the prevalence of LBP was higher in older people when compared to younger age groups [20]. These findings are in line with those reported by Heissam (2015) and Emmanuel and Ezhilarasu (2016) [24,25].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The link between getting older and developing lower back pain is complicated and can be further complicated by several other factors. According to the findings of the study by Alemam (2022), the prevalence of LBP was higher in older people when compared to younger age groups [20]. These findings are in line with those reported by Heissam (2015) and Emmanuel and Ezhilarasu (2016) [24,25].…”
Section: Discussionsupporting
confidence: 87%
“…Alemam (2022) found that low back pain was significantly more common in females than in males. The percentage of females diagnosed with low back pain was 73.4%, while the percentage of males diagnosed with low back pain was 47.8% [20].…”
Section: Discussionmentioning
confidence: 92%
“…Female rather than male were found to have a signi cant association with chronic back pain this variation could be related to the anatomical, physiological, and structural differences between both gender and females tended to do extra professional activities in the household. This association is reported in the previous studies conducted in Egypt, Italy, Saudi Arabia and Turkey [11][12][13] The doctors were found to be the most complaining of chronic back pain as they represent 62.5% among health worker. Nurses come the second as they represent 18.1%.…”
Section: Discussionsupporting
confidence: 76%
“…This nding is attributed to similarity of work setting and health delivery system [7][8][9]. However, many other studies reported higher incidence of chronic pain [10][11][12]. Which is justi ed by differences in methods used, socio-economic status and socio-demographic distribution in these countries.…”
Section: Discussionmentioning
confidence: 99%